Taiwan’s E-Government Usability from Foreign Perspective and Website Accessibility amid COVID-19 Pandemic - Husam ALmaghalsah; Chia-Hua Chang (Journal of Business and Behavioural Entrepreneurship, 2021)
The aim of this research intends to investigate Taiwanese egovernment websites with regards to Accessibility and Usability. The automated WAVE Accessibility tool and Nielsen’s 10 Heurestic Principle based surveys of foreign users of the English egovernment websites were used to test Accessibility and Usability respectively. The study found poor results that were unanimous across the board for Usability and total of just over 100 errors for Accessibility was the best performing website. The study proves that further research and investigation is necessary if Taiwan wants to meet its own governmental ambitions with regards to egovernment.